2016
DOI: 10.1111/ases.12326
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy‐assisted distal gastrectomy in a case of gastric cancer with situs inversus totalis: a case report

Abstract: Situs inversus totalis (SIT) is a rare congenital condition in which abdominal and thoracic organs are transposed from normal positions. Laparoscopy-assisted distal gastrectomy for situs inversus totalis is technically difficult and has rarely been reported. Here, we report the case of man in his 40s with situs inversus totalis and a preoperative diagnosis of stage IA gastric cancer (cT1b, cN0, cM0). We successfully performed laparoscopy-assisted distal gastrectomy with D1+ lymph node dissection and Billroth I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Therefore, the position of the surgeon relative to the patient presents an important problem when performing laparoscopic gastrectomy in a patient with SIT. Previous reports on laparoscopic gastrectomy in patients with SIT indicated that the main surgeon stood where they normally would when performing surgery in a patient without SIT in only half of the cases; the surgeon stood on the opposite side in the other half (2,6,9,11–13, Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the position of the surgeon relative to the patient presents an important problem when performing laparoscopic gastrectomy in a patient with SIT. Previous reports on laparoscopic gastrectomy in patients with SIT indicated that the main surgeon stood where they normally would when performing surgery in a patient without SIT in only half of the cases; the surgeon stood on the opposite side in the other half (2,6,9,11–13, Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgical procedures can be difficult in patients with SIT because of the anatomical abnormality, which represents a mirror image of the normal location, laparoscopic surgery has been performed more often in recent years (4, 6, 7, 9-12, 14-17, 19, 20). The surgical procedures undertaken for the present case were not significantly different from standard procedures in patients without SIT, although in any case with SIT, it is important to confirm the vascular locations on preoperative diagnostic imaging modalities, including CT or angiography, because SIT often displays abnormal vascularization of both the arteries and veins (16). In conclusion, superficial spreading-type gastric cancer with SIT is an extremely rare entity, and in such cases the surgical team should carefully ascertain the specific vascular anatomy by preoperative diagnostic imaging in order to optimize procedural success.…”
Section: Discussionmentioning
confidence: 69%
“…LG for gastric cancer was first performed in 1991 [ 21 ], and LG with lymph node dissection for advanced gastric cancer is now well developed in Japan [ 22 ] and considered safe and feasible [ 23 , 24 ]. The first case of laparoscopic-assisted distal gastrectomy for SI patients with gastric cancer was reported in 2003 [ 25 ], and several cases have since been documented [ 5 , 7 , 25 ]. However, almost all were cases of SIT.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgeons have performed laparoscopic gastrectomy (LG) in SI patients [ 5 7 ], but all patients were categorized as SIT. Only one case of robot-assisted distal gastrectomy (RADG) in an SI patient has been reported, and robotic surgery is considered suitable only in SIT patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%